2013
DOI: 10.12681/mms.425
|View full text |Cite
|
Sign up to set email alerts
|

Using guarding net to reduce regularly discarded invertebrates in trammel net fisheries operating on seagrass meadows (Posidonia oceanica) in Izmir Bay (Eastern Aegean Sea)

Abstract: Prohibition of both beach and boat seines and trawl fishery along the İzmir Bay coasts in the Aegean Sea signifies intensive usage of gillnets and trammel nets, for catching red mullet (Mullus spp.) species in particular. Trials were realized between March 2009 and February 2010 with trammel nets in the areas on the boundaries of the sea grass (Posidonia oceanica) meadows in the Bay. Guarding net (selvedge) was attached to the lead line of experimental nets (Exp1-Exp2) - 36 and 40 mm inner panel. Differences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
3
13
1
Order By: Relevance
“…The significant reductions in discards observed in the present study when using a guarding net on the lead line are in general agreement with previous studies on reduction techniques for gill and trammel net fisheries in the Mediterranean (Gökçe, ; Metin et al., ; Aydin et al., ). Also the insignificant reduction of the catch of target species (green tiger prawn for this study) was similar to results reported by Metin et al.…”
Section: Discussionsupporting
confidence: 93%
“…The significant reductions in discards observed in the present study when using a guarding net on the lead line are in general agreement with previous studies on reduction techniques for gill and trammel net fisheries in the Mediterranean (Gökçe, ; Metin et al., ; Aydin et al., ). Also the insignificant reduction of the catch of target species (green tiger prawn for this study) was similar to results reported by Metin et al.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with previous studies such as those performed in Izmir Bay and Antalya in Turkey (Metin et al 2009, Olguner and Deval 2013, Aydin et al 2013, the modified trammel net used in the present study did not provide similar successful outcomes; although there was a reduction in by-catch, there was also a loss of earnings of target species and commercial by-catch. Vecchioni et al (2016) also reported decreased discard rates for modified trammel nets and decreased yield of commercial species in experimental trials with modified and standard trammel nets in the Egadi marine protected area in Italy, while Sartor et al (2007) found that trammel nets with a guarding net from the Livorno coast (Italy) had lower catches of more benthic commercial species than standard trammel nets.…”
Section: Guarding Net: a Successful Modification?contrasting
confidence: 92%
“…In another study performed in Izmir Bay on Mullus spp. fishery (Aydin et al 2013), discard rates decreased to about 55% to 63%, and the guarding net reduced the catches of the three main by-catch taxa (Hexaplex trunculus, Bolinus brandaris, Maja spp. ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, damage reduction has been reported when greca was used in red mullet ( Mullus spp.) and shrimp ( Melicertus kerathurus ) fisheries at the Aegean Sea ( Metin et al, 2009 ; Aydin, Gökçe & Metin, 2013 ). In these cases, the reduction of net damage was attributed to a reduced bottom contact of the net with the seabed and the avoidance of capturing benthic invertebrates that appear to be selectively excluded by the greca .…”
Section: Discussionmentioning
confidence: 99%